Bioresorbability Evaluation of Hydroxyapatite Nanopowdersin a Stimulated Body Fluid Medium: Bioresorbability of hydroxyapatite nanopowders - Arash Hanifi; Mohammad Hossein Fathi (Iranian Journal of Pharmaceutical Sciences, 2008)
The bone mineral consists of tiny hydroxyapatite (HA) crystals in the nanoregime.Nanostructured HAis also expected to have better bioactivity than coarser crystals.This paper reports on the in vitroevaluation of bone like HAnanopowders. The prepared HAnanopowder was characterized for its phase purity, chemical homogeneity and bioactivity. Fourier transform infrared (FT-IR) spectroscopy was used to identify the functional groups. X-ray diffraction analysis was carried out to study the phase composition. The in vitrotest was performed in a stimulated body fluid medium. The changes in the pH of SBF medium were measured at pre-determined time intervals using a pH meter. The dissolution of calcium ions in the SBF medium was determined by an atomic absorption spectrometer. FT-IR spectroscopy result combined with the X-ray diffraction exhibited single phase of HAwith carbonate peaks in the FT-IR spectrum. Results indicated that increasing the sintering temperature increases the crystallinity and the crystallite size of HA nanopowders. HAnanopowders ionic dissolution rate was found to be quite higher than conventional HAand closer to biological apatite owing to its nanostructure dimensions.